Understanding Social Entrepreneurial Intention Through Social Cognitive Career Theory: a Partial Least Squares Structural Equation Modelling Approach - Aure, Patrick Adriel P.; Dui, Rayan P.; Jimenez, Shieradel V.; Daradar, Denver D.; Gutierrez, Alvin Neil A.; Blasa, Angelique C.; Sy-Changco, Joseph (Organizations and Markets in Emerging Economies, 2019)
This research attempted to find empirical evidence that examines the drivers of social entrepreneurial intentions (SEI) through the lens of social cognitive career theory (SCCT).  Since the SCCT model of SEI is still in the early stages and needs to be further developed, experts recommend the use of partial least squares structural equation modelling (PLS-SEM) to analyze data collected from 294 business students from a Philippine university.  To account for observed heterogeneity, differences among senior high school and college business students were explored via multigroup analysis (PLS-MGA).  Across all respondents, perceived support and internal outcome expectations have the strongest total effects on SEI, while self-efficacy and agreeableness have marginally significant direct effects and significant indirect effects on SEI.  This study contributed to the field of social entrepreneurship by looking at alternate and developing explanations to the formation of SEI apart from conceptual models based on the theory of planned behavior.
Keywords: Social entrepreneurial intentions; partial least squares structural equation modeling; social cognitive career theory